The determination of drag in the gliding phase in swimming - Marinho, D.; Carvalho, F.; Barbosa, T.; Reis, V.; Alves, F.; Rouboa, A.; Silva, A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The hydrodynamic drag forces produced by the swimmer during the sub aquatic gliding have been analyzed appealing to experimental investigation methods (e.g., Lyttle et al., 2000). However, the obtained results varied, which can translate some of the main inherent difficulties involved in the experimental studies. Thus, through application of a numerical method of Computational Fluid Dynamics (CFD), we intended to study the hydrodynamic drag forces, created during the displacement of the swimmer in different gliding positions, attempting to address some practical concerns to swimmers and coaches.